2008
DOI: 10.1016/j.ajhg.2007.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M Receptor-β Mutations Underlie Familial Primary Localized Cutaneous Amyloidosis

Abstract: Familial primary localized cutaneous amyloidosis (FPLCA) is an autosomal-dominant disorder associated with chronic skin itching and deposition of epidermal keratin filament-associated amyloid material in the dermis. FPLCA has been mapped to 5p13.1-q11.2, and by candidate gene analysis, we identified missense mutations in the OSMR gene, encoding oncostatin M-specific receptor beta (OSMRbeta), in three families. OSMRbeta is a component of the oncostatin M (OSM) type II receptor and the interleukin (IL)-31 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
131
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 26 publications
(32 reference statements)
5
131
0
1
Order By: Relevance
“…Within this critical region, Arita et al 22 have replicated the linkage data for chromosome 5p13.1-q11.2 in a large Brazilian family. Moreover, they identified a missense mutation (c.2072T4C; p.I691T) in all affected individuals in the OSMR gene, encoding oncostatin M-specific receptor b (OSMRb).…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…Within this critical region, Arita et al 22 have replicated the linkage data for chromosome 5p13.1-q11.2 in a large Brazilian family. Moreover, they identified a missense mutation (c.2072T4C; p.I691T) in all affected individuals in the OSMR gene, encoding oncostatin M-specific receptor b (OSMRb).…”
Section: Introductionsupporting
confidence: 56%
“…None of the 142 control subjects from Taiwan (or over 250 control chromosomes from other populations) showed presence of p.P694L or the other missense mutations. All these amino-acid substitutions occur within the fibronectin III-like domains of OSMRb, in a similar location to the mutations reported by Arita et al 22 No mutations in OSMR were identified in the other 19/29 pedigrees, including eight pedigrees that showed linkage to the chromosome 5 interval.…”
Section: Linkage Replication Studymentioning
confidence: 64%
See 2 more Smart Citations
“…Although Oncostatin M Receptor (OSMR) gene and IL3IRA mutations has been reported. 1,6,8 P.L.C.A consists of macular and lichen amyloidosis, and sometimes both forms may co-exist. Rare forms are bullous, vitiliginous or ichthyosiform amyloidosis.…”
Section: Introductionmentioning
confidence: 99%